Meningkatkan Hasil Belajar Siswa pada Materi Benda Zat Tunggal dan Campuran Melalui Model Snowball Throwing dan Media Kartu Pintar Kelas V SDN Talaga Jaya - Rahmatia Suleman; Irvin Novita Arifin; Gamar Abdullah (EduInovasi: Journal of Basic Educational Studies, 2024)
Rahmatia Suleman, 2024. Improving the Learning Outcomes of Pure Substance and Mixtures Material using Snowball Throwing Model and Smart Card Media for Students in Class V of SDN 3 Talaga Jaya. Undergraduate Thesis. Department of Elementary Teacher Education, Faculty of Education, Universitas Negeri Gorontalo. The principal supervisor is Dr. Irvin Novita Arifin, S.Pd., M.Pd., and the co-supervisor is Dr. Gamar Abdullah, S.Si., M.Pd.The problem statement of this research is "Can the implementation of Snowball Throwing Model and Smart Card Media improve the learning outcomes of students in class V of SDN 3 Talaga Jaya?" This Classroom Action research aims to improve the learning outcomes of Pure Substance and Mixtures material using the Snowball Throwing Model and Smart Card Media for students in class V of SDN 3 Talaga Jaya.The result gained from 27 students shows that in the early stage observation the learning outcome indicator reached 22.22% (6 students). In cycle I there were 52% (14 students) completed the Minimum Completion Criteria. Concluding it did not thrive enough, cycle II was held with the result of 86% (23 students) who completed the Minimum Completion Criteria. Overall, the percentage escalated to 34%. Therefore, it can be concluded that the Snowball Throwing Model and Smard Card in learning Pure Substance and Mixtures improved the learning outcomes of students in class V of SDN 3 Talaga Jaya.